2013
DOI: 10.1037/a0029188
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of effectiveness of complementary and adjunct therapies and interventions involving equines.

Abstract: In the aggregate, the evidence is promising in support of the effectiveness of complementary and adjunct interventions employing equines in the treatment of health challenges. Future studies are needed that utilize rigorous and creative designs, especially longitudinal studies and comparisons with established effective treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 43 publications
(100 reference statements)
0
56
0
7
Order By: Relevance
“…A recent systematic review11) of 14 EAA/T studies have validated psychotherapeutic effectiveness that significant biopsychosocial outcomes have been achieved, such as decreased negative affect, improvement of adaptive functioning, and perceived wellness. In addition, a randomized controlled trial demonstrated that children with autism spectrum disorder who received 10-week therapeutic horseback riding showed not only significant improvement in social cognition, communication and expressive language but also irritability and hyperactivity behaviors compared to barn activity control groups 12).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review11) of 14 EAA/T studies have validated psychotherapeutic effectiveness that significant biopsychosocial outcomes have been achieved, such as decreased negative affect, improvement of adaptive functioning, and perceived wellness. In addition, a randomized controlled trial demonstrated that children with autism spectrum disorder who received 10-week therapeutic horseback riding showed not only significant improvement in social cognition, communication and expressive language but also irritability and hyperactivity behaviors compared to barn activity control groups 12).…”
Section: Introductionmentioning
confidence: 99%
“…Kendall and colleagues (2015) report that although additional rigorously-designed studies were needed to conclude that equine-assisted interventions are efficacious, "equine-assisted interventions hold much promise, particularly in terms of child/adolescent social and behavioural issues" (p. 75). Selby and Smith-Osborne (2013) found a similarly small group of studies for review of equine-assisted therapy for populations with chronic illness or health conditions, noting that their analyses "lend credibility to the employment of equine-assisted techniques as an adjunct to traditional interventions for populations with health challenges" (p. 428).…”
Section: The Evidence For Equine-assisted Therapymentioning
confidence: 99%
“…It is impressive that this effect is robust across the variations in treatment programs. Systematic reviews of using horses in psychotherapy also indicate that interventions are promising for a range of populations (Kendall et al, 2015;Selby & Smith-Osborne, 2013). Kendall et al (2015) identified 15 studies that qualified for inclusion in their review.…”
Section: The Evidence For Equine-assisted Therapymentioning
confidence: 99%
“…A recent systematic narrative review by Selby and Smith‐Osborne () examined the effectiveness of complementary and adjunctive interventions involving equines. The authors did not restrict their review to the use of ERT in the treatment of mental illness; instead, they reported results from several trials examining such outcomes and referenced several others.…”
mentioning
confidence: 99%
“…The authors did not restrict their review to the use of ERT in the treatment of mental illness; instead, they reported results from several trials examining such outcomes and referenced several others. The authors concluded that the overall results were promising and justified consideration of ERT as a potentially useful adjunctive approach in the treatment of mental illness (Selby & Smith‐Osborne, ). The review did not speak directly to the utility of ERT as a standalone treatment; however, the treatment is often marketed as such (e.g., PATH International, ) and the financial costs associated with treatment are often substantial (e.g., SouthSource, ; True Balance PLLC, ).…”
mentioning
confidence: 99%